Pemberdayaan Masyarakat dan Pariwisata dalam Pengelolaan Bencana Alam di Pantai Widarapayung - Rokalina Rokalina; Suwarno Suwarno (Proceedings Series on Social Sciences & Humanities, 2022)
The prospect of the tourism industry in Indonesia is very large and promising considering that Indonesia has abundant natural resources, one of which is in the coastal sector. By empowering the community, people can increase their knowledge and ability to be able to identify problems, plan, and implement solutions by utilizing local potential and existing facilities, such as disaster management. This study aims to determine the efforts made for community empowerment and tourism in disaster management on the Widarapayung beach. This type of research uses descriptive qualitative research. The subjects of this research are the widarapayung beach manager, the widarapayung village apparatus, the widarapayung community and related institutions. Data collection techniques were carried out through observation, literature review and documentation. The data analysis technique used is data reduction, data presentation, conclusion drawing and verification. Based on the results of research with SWOT analysis, in community empowerment and tourism at Widarapayung Beach, it is necessary to apply eight strategies in disaster management, namely planning, organizing, leadership, coordinating, controlling, monitoring, budgeting and finance.